Inovasi Manajemen Talenta Aparatur: Analisis SWOT dan Perencanaan Strategis BKPSDM Kabupaten Solok untuk Transformasi Birokrasi 2025–2030 - Herlina; Syafwandi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study designs a SWOT-based strategic plan for talent management transformation at BKPSDM Solok Regency (2025–2030). Using a descriptive qualitative approach, it identifies internal-external factors in local government HR management. Data collected through in-depth interviews (12 key informants), document analysis (RPJMD/Strategic Plans), and field observations (8 service units). Findings reveal: (1) Core strengths in HR competency (68% Master/PhD) and SIMPEG support; (2) Critical weaknesses in training budget deficit (<15% needs) and bureaucratic inertia; (3) Strategic opportunities via triple helix collaboration; (4) Threats of inter-regional incentive disparities. The strategic plan features three pillars: digital talent ecosystem, agile bureaucracy, and merit-based leadership. Evaluation employs Balanced Scorecard with four performance perspectives.